Organic Rankine Cycle and its application in renewable power engineering - G. V. Belov (Nauka i Obrazovanie, 2014)
A considerable part of energy consumed in the world is thermal power that is produced due to burning of hydrocarbon fuels and as a result of controlled course of nuclear reactions. Thus rather large part of thermal power is used ultrainefficiently, often simply dissipates in environment. The rise in prices for energy compels to use low-grade one to be released in large quantities in environment. To utilize the low-grade energy Renkin's cycle with with alternative working bodies is often applied. The corresponding cycle was called Renkin's organic cycle (ROC). A substance with lower boiling temperature, than that of water is used in ROC as a working body to utilize low-grade energy. The review of literature shows that thrust on power sector related to utilization of residual heat (thermal waste) and use of alternative energy sources, recently, intensively develops. However there is, essentially, a lack of publications on this subject in Russian. The objective of given article is to analyse modern sources of information (mainly, foreign ones) which consider various aspects of ROC and its application potential in alternative power engineering. The article focuses much attention on the choice of ROC working body. It presents a list of main requirements for a working body. The article studies the matters of ROC simulation. It is shown that ROC application enables using the low-grade power of exhaust gases, geothermal sources, other thermal streams with rather low temperature. Integration of ROC with ICE (internal combustion engine) is in position to increase an efficiency of used fuel energy and to reduce amount of toxic impurity in exhaust gases. Essential influence of working body properties on its characteristics of ROC is noted.